(untitled) (Prilozi za orijentalnu filologiju, 2017)
The paper presents the structure and some general poetic features of Diwan by Ahmad Rushdi Mostari Sahhaf, one of Mostar’s most notable 17th century diwan poets. Qasidas are analysed in particular by the theory of “unity of distich/verse” (wahdat al-bayt) in diwan literature. In describing the poetic quality of Rushdi’s ghazels, some attention is paid to the phenomenon of semantic and lexical focus in the light of determination of the ghazel style dominant. The chapter about a/historicity of the chronogram is a survey of major chronograms written by Ahmad Rushdi Mostari. Another feature of Ahmad Rushdi Mostari’s Diwan is a large number of matla‘s (403). The paper is only an introduction to the poetics of Diwan by Ahmad Rushdi Mostari.